Identification and Characterization of a Garlic Virus E Genome in Garlic (Allium sativum L.) Using High-Throughput Sequencing from India - Malyaj R. Prajapati; Aakansha Manav; Jitender Singh; Pankaj Kumar; Amit Kumar; Ravindra Kumar; Satya Prakash; Virendra Kumar Baranwal (Plants, 2022)
Garlic (Allium sativum L.) plants exhibiting mosaics, deformation, and yellow stripes symptoms were identified in Meerut City, Uttar Pradesh, India. To investigate the viruses in the garlic samples, the method of high-throughput sequencing (HTS) was used. Complete genome of the garlic virus E (GarV-E) isolate (NCBI accession No. MW925710) was retrieved. The virus complete genome comprises 8450 nucleotides (nts), excluding the poly (A) tail at the 3′ terminus, with 5′ and 3′ untranslated regions (UTRs) of 99 and 384 nts, respectively, and ORFs encoding replicase with a conserved motif for RNA-dependent RNA polymerase (RdRP), TGB1, TGB2, TGB3, serine-rich protein, coat protein, and nucleic acid binding protein (NABP). The sequence homology shared 83.49–90.40% and 87.48–92.87% with those of GarV-E isolates available in NCBI at the nucleotide and amino acid levels, respectively. Phylogenetic analysis showed a close relationship of this isolate from India (MW925710) with GarV-E isolate YH (AJ292230) from Zhejiang, China. The presence of GarV-E was also confirmed by RT-PCR. The present study is the first report of GarV-E in garlic cultivar Yamuna Safed-3 grown in northern India. However, further studies are needed to confirm its role in symptom development, nationwide distribution, genetic diversity, and potential yield loss to the garlic in India.